The mitochondrial negative regulator MCJ is a therapeutic target for acetaminophen-induced liver injury - Lucía Barbier-Torres (Nature Portfolio, 2017)
Acetaminophen-induced liver injury is one of the most common causes of liver failure and has to be treated within hours of the overdose. Here Barbier-Torres et al. show that targeting MCJ, a mitochondrial negative regulator, even 24 h after the overdose protects liver from acetaminophen-induced damage.